2020
DOI: 10.12750/jarb.35.2.171
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Equilume light masks on the timing of seasonal ovulation of Thoroughbred mares in South Korea

Abstract: Advancing the estrous cycle of mares is an essential breeding strategy that is routinely conducted by Thoroughbred breeders to improve economic outcomes. For this purpose, Equilume light masks have been developed as an alternative to existing technologies such as artificial lighting or hormonal treatments because they are considered as valid as existing methods with additional animal welfare advantages. For example, with the Equilume light masks, horses can be let out into the pasture, whereas they have to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
3
3
Order By: Relevance
“…However, our study findings were different from the previous assessment of the effect of the Equilume light masks on hastening the reproductive cycle parameters of mares [ 25 ]. Results of the reproductive examinations conducted in February showed that several mares exposed to blue light treatment exhibited estrus cycles and ovulation in Jeju Island, whereas none of the mares previously examined at this time exhibited ovarian activity when maintained at locations inland in Korea [ 25 ]. The BCS for the mares were not significantly different from that of the previous research, but the temperature was significantly different [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, our study findings were different from the previous assessment of the effect of the Equilume light masks on hastening the reproductive cycle parameters of mares [ 25 ]. Results of the reproductive examinations conducted in February showed that several mares exposed to blue light treatment exhibited estrus cycles and ovulation in Jeju Island, whereas none of the mares previously examined at this time exhibited ovarian activity when maintained at locations inland in Korea [ 25 ]. The BCS for the mares were not significantly different from that of the previous research, but the temperature was significantly different [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, unpublished data collected by an experienced veterinarian involved in this study and who has worked within the Thoroughbred breeding industry on Jeju Island for more than twenty years suggests that the mean date of first ovulation in unlit mares occurs between late March and early April. A similar experimental design to the current study was employed previously to evaluate light therapies at advancing seasonal reproductive activity in mares However, our study findings were different from the previous assessment of the effect of the Equilume light masks on hastening the reproductive cycle parameters of mares (25). Results of the reproductive examinations conducted in February showed that several mares exposed to blue light treatment exhibited estrus cycles and ovulation in Jeju Island, whereas none of the mares previously examined at this time exhibited ovarian activity when maintained at locations inland in Korea (25).…”
Section: E T E Dcontrasting
confidence: 60%
See 2 more Smart Citations
“…36, No. 2, June 2021 100 mone, seasonal effect to reproductive organ, device for controlling seasonal effect and biotechnology for embryo transfer (Park et al, 2017;Yu et al, 2017;Lee et al, 2020;Seong et al, 2020). Especially, the foaling is considered as one of main topics among several fields of reproductive physiology of mares.…”
Section: Introductionmentioning
confidence: 99%